2016
DOI: 10.1007/s13277-016-4885-5
|View full text |Cite
|
Sign up to set email alerts
|

The cancer-retina antigen recoverin as a potential biomarker for renal tumors

Abstract: The renal cell carcinoma is the ninth most common cancer with an increasing occurrence and mortality. Recoverin is the first retina-specific photoreceptor protein that was shown to undergo aberrant expression, due to its promoter demethylation, as a cancer-retina antigen in a number of malignant tumors. In this work, we demonstrated that recoverin is indeed expressed in 68.4 % of patients with different subtypes of renal cell carcinoma, and this expression has tendency to correlate with tumor size. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
10
0
4
Order By: Relevance
“…Thus, the identification of the tumor transcriptome and proteome to identify more immunogenic TSAs is helpful. Several highly immunogenic TSAs have already been described [260][261][262][263]. However, modern methods such as high-throughput sequencing technologies and bioinformatics analysis of big data allow the identification of new tumor antigenic determinants, such as neoantigens [264,265].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the identification of the tumor transcriptome and proteome to identify more immunogenic TSAs is helpful. Several highly immunogenic TSAs have already been described [260][261][262][263]. However, modern methods such as high-throughput sequencing technologies and bioinformatics analysis of big data allow the identification of new tumor antigenic determinants, such as neoantigens [264,265].…”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 , 8 Prior histologic studies have demonstrated that oncocytomas can produce known retinal antigens, including recoverin and neuron-specific (gamma) enolase. 9 , 10 This patient did not have anti-recoverin or anti-gamma enolase antibodies in his serum, and staining of the oncocytoma was negative for gamma enolase.…”
Section: Discussionmentioning
confidence: 94%
“…Исследования показывают [1][2][3], что многие заболевания полости рта значимо влияют на риски развития плоскоклеточного рака (ПЛР) слизистой оболочки полости рта (СОПР) [4][5][6]. Так, острые края зубов, протезов и пломб могут быть причиной хронической травмы СОПР [7,8], а наличие зубных отложений поддерживает хроническое воспаление пародонта [9,10], что в совокупности может инициировать развитие ПЛР.…”
Section: терапевтический разделunclassified